Coordinated control of networked vehicles: An autonomous underwater system - F. Lobo Pereira (2004)
The specification and design of coordinated control strategies for networked vehicle systems are discussed. The discussion is illustrated with an example of the coordinated operation of two teams of autonomous underwater vehicles collecting data to find the local minimum of a given oceanographic scalar field.